ANALISIS KETERKAITAN STRUKTUR DAN PRINSIP SAINS DENGAN KONSEP MATEMATIKA DALAM KONTEKS PENDIDIKAN - Wardani, Az-Zahra Ayu; Jiofani, Marsheila; Khoirulloh, Ahmad Hilmy; Amir; Ikmawati; Kurniawan (CV. ADIBA ASIHA AMIRA, 2025)
In the realm of science, mathematics functions as a universal language that enables observed facts to be expressed as organized laws and theories. This study aims to analyze the relationship between the structure and principles of science with mathematical concepts, as well as to examine their impact on the learning process. The method employed is a literature review by collecting and analyzing articles published between 2019 and 2025. Relevant articles were selected, compiled, and compared to identify patterns of connection between science and mathematics. The findings indicate that mathematics serves as a crucial foundation in explaining scientific principles across various fields, such as physics, chemistry, and biology, through equations, graphs, and mathematical models. In the context of education, integrating science and mathematics enhances conceptual understanding, critical thinking, and the skills required in the 21st century. Furthermore, the synergy between the two also fosters innovation in technological development and interdisciplinary research that aligns with the needs of modern society. This study emphasizes that mastery of mathematics is inseparable from science, and therefore both should be integrated into curriculum design and modern learning approaches